2022
DOI: 10.1097/ncc.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gastrointestinal Symptoms Are Associated With Chemotherapy-Induced Nausea in Patients With Breast Cancer

Abstract: BackgroundUnrelieved chemotherapy-induced nausea (CIN) is a significant problem for patients with breast cancer (BC).ObjectiveIn a sample of patients with BC who were assessed before their second or third cycle of chemotherapy, study purposes were to evaluate for the occurrence, severity, frequency, and distress associated with CIN; evaluate for differences in demographic and clinical characteristics and gastrointestinal (GI) symptom occurrence rates between patients who did and did not report CIN; and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…This study showed that there was a significant negative correlation between dietary intake and signs of malnutrition. This result was in agreement with Casari (2021) who mentioned that no significant association between nutritional status and gastrointestinal symptoms was found( 58,59)…”
Section: Tablesupporting
confidence: 93%
“…This study showed that there was a significant negative correlation between dietary intake and signs of malnutrition. This result was in agreement with Casari (2021) who mentioned that no significant association between nutritional status and gastrointestinal symptoms was found( 58,59)…”
Section: Tablesupporting
confidence: 93%
“…The items in this questionnaire in the part of digestive function component are not different from several studies. Eating, nausea and vomiting, and constipation were the most frequently occurring symptoms during chemotherapy (Ward Sullivan et al, 2018;Singh et al, 2022). Chemotherapy-induced nausea and vomiting (CINV) are associated with a significant deterioration in QoL, affecting the comfort levels of patients experiencing this symptom (Navari, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study include the use of dietary self-reports, which rely on memory and have the potential for under-reporting of foods—a recognized caveat in nutrition research [ 62 , 63 ]. This study also did not measure gastrointestinal symptoms common during cancer treatment, such as nausea, vomiting, dry-mouth, constipation, changes in taste and loss of appetite, all of which may impact diet [ 64 , 65 ]; though it must be noted that all women included in this study had completed treatment at least 3 years prior to the dietary recalls. Future studies including the long-term effects of cancer treatment on GI function might elucidate the potential for long-term adverse effects affecting the potential for consuming a high-quality diet.…”
Section: Discussionmentioning
confidence: 99%